Pricing Strategy for Cloud Computing: A Damaged Services Perspective. - HUANG, Jianhui (Institutional Knowledge at Singapore Management University, 2015)
How effective is a hybrid pricing strategy for a cloud computing services vendor that mixes fixed-price reserved services with spot-price on-demand services? This research offers a decision support model to create the appropriate strategy for IT services based on prior research on information goods, electricity pricing, product versioning, and revenue yield management. The goal is to establish whether interruptible spot-price on-demand cloud computing services — which we view as damaged services — are valuable to the vendor. The results from the analysis of an economic model show that a hybrid strategy outperforms a one-service-only strategy in most cases, especially when clients are sensitive to services interruptions or when task values are highly differentiated. A more intriguing finding is that a vendor should permit the possibility of services interruptions even when clients are highly sensitive to their occurrence. The presence of interruptions serves as a quality differentiator between the on-demand services and reserved services, assuring the efficacy of the hybrid strategy. Moreover, a vendor may use capacity limit, in the hybrid strategy, as a tool to further improve its profit. To our knowledge, this research is the first to propose the damaged services perspective as an analogy for damaged goods in the cloud software market.